Social Media As A Marketing Media For Pandansari Mangrove Forest Tourism Object - Nur Andina, Anisa; Zain Ramadhan, Rafif; Leginasawati, Hasna (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Facing the industrial revolution 4.0 which makes technology development even more rapid making the world of tourism in Indonesia also progresses. Tourism that is experiencing development certainly provides additional foreign exchange for the country. Brebes Regency as a district that has many hidden tourism treasures is currently one of the regencies in Central Java that is quite reckoned with in the world of tourism. The purpose of this study are to see how much social media impact has in order to enlarge the number of visitors in Pandansari mangrove forest at Kaliwlingi Village Brebes Regency through tourism promotion. The idea of marketing through social media is currently the new prima donna. Social media is used to market tourism objects more broadly. Reaching larger audiences, the work of social media continues to be improved mainly in attracting potential visitors who have never come to this place at all. The analysis object in this paper is the social media account belonging to the Pandansari mangrove forest located in Kaliwlingi Village Brebes Regency which is often referred to as Dewi Mangrovesari. Using descriptive qualitative research technique, it was found that the use of social media as marketing was effective because currently people are very familiar with technology. Good management and efforts to preserve the environment are also one of the things promoted by the Pandansari mangrove forest tourism object.